Crystal engineering with coordination, hydrogen- and halogen-bonds, and the construction of porous solids - Gunawardana, Chamara Abeywickramasinghe (Kansas State University, 2018)
A set of multifunctional molecules [isomeric forms of 1-(pyridylmethyl)-2,2'-biimidazole] was synthesized and subjected to systematic co-crystallizations with selected hydrogen- and halogen-bond donors in order to explore the impact of interaction type, geometry and electrostatics on the resulting supramolecular architectures. The structural outcome with hydrogen-bond donors (carboxylic acids) is somewhat unpredictable because of the presence of the acid···biimidazole heterosynthon that can compete with biimidazole···biimidazole homosynthon. In contrast, the solid-state supramolecular behavior of those probe molecules is largely unchanged in halogen-bonded co-crystals. Only two types of primary interactions, the two-point hydrogen bonds responsible for pairing biimidazole moieties, and the single-point halogen bonds responsible for the co-crystal formation and structure extension, are present in these systems. The results highlight that, by incorporating geometric biases along with orthogonal interactions, one can effectively prevent synthon crossover which is of paramount importance in complex crystal engineering endeavors. Heterobifunctional ligands pave the way for elaborate metallo-supramolecular systems, and are also useful for combining metal-ligand bonding with other types of non-covalent interactions. Nine new acetylacetonate ligands featuring either pyridyl- or thiophenyl-heterocycles were successfully prepared, and their metal binding abilities were studied with selected di- and tri-valent transition metal ions. As expected, the acetylacetonate ligation to metal dications remains consistent. In each case, the metal is four-coordinate and resides in a square planar environment. Differences in the overall architectures arise from the role played by the terminal heterocycles and the solvent. In seven (out of nine) structures, the heterocyclic end is involved in a structure-directing interaction and it is more prevalent in ligands bearing 4-pyridinyl unit. Divergent molecules containing bulky substituents tend to produce porous materials via frustrated packing. Two rigid tetrahedral cores, tetraphenylmethane and 1,3,5,7-tetraphenyladamantane, grafted peripherally with four (trimethylsilyl)ethynyl moieties were found to have only isolated voids in their crystal structures. Hence, they were modified into tecton-like entities, tetrakis(4-(iodoethynyl)phenyl)methane [I₄TEPM] and 1,3,5,7-tetrakis(4-(iodoethynyl)phenyl)adamantane [I₄TEPA], and the effect of motif-forming characteristics of iodoethynyl units on molecular arrangement and crystal porosity was analyzed. I₄TEPM not only holds increased free volume compared to its precursor, but also forms one-dimensional channels. Furthermore, it readily co-crystallizes with Lewis basic solvents to afford two-component porous materials even though they suffer from stability issues. As the binding sites in I₄TEPM and I₄TEPA are tetrahedrally-predisposed, they can be further utilized for the modular assembly of highly symmetric, three-dimensional extended architectures. With that in mind, these two building blocks were subsequently allowed to react with various halide salts, and it was found that the reactions between I₄TEPM and tetraphenylphosphonium halides readily yield four-fold interpenetrated diamondoid networks sustained by C–I⋯X⁻ (X⁻ = chloride, bromide, iodide) halogen-bonding interactions. The halide anions exhibit mutual-induced fitting of their coordination and act as four-connecting tetrahedral nodes, while the tetraphenylphosphonium cations render essential templating information and structural support.
Keywords: Supramolecular chemistry; Crystal engineering; Molecular porous material; Heterobifunctional ligand; Diamondoid network; Coordination polymer